2004
DOI: 10.1016/s0168-6496(04)00003-0
|View full text |Cite
|
Sign up to set email alerts
|

Plant colonization by pink-pigmented facultative methylotrophic bacteria (PPFMs)

Abstract: Bacteria belonging to the genus Methylobacterium are characterized by being able to rely on methanol as a sole carbon and energy source and by presenting a more or less intense pink reddish pigmentation. These bacteria, also referred to as pink-pigmented methylotrophic bacteria (PPFMs), are common inhabitants of the phyllosphere and are found in many other environmental samples. Since they grow slowly they are often overlooked and their impact on phyllosphere microbial communities and on the plants harboring t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
60
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 26 publications
(40 reference statements)
2
60
0
6
Order By: Relevance
“…Omer et al (2004) has reported that PPFMs isolated from red clover readily colonized winter wheat leaves and vice versa in greenhouse experiments, and that the tested isolates had good potential to colonize the rhizosphere, especially after seed inoculation. 8) According to Knief et al (2010), factors specific to the sites from which the plant species were collected, more than the plant species themselves, have a strong influence on the composition of the phyllospheric Methylobacterium community. 14) We found that PPFMs were highly abundant on perilla leaves, regardless of the geographic site from which they were collected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Omer et al (2004) has reported that PPFMs isolated from red clover readily colonized winter wheat leaves and vice versa in greenhouse experiments, and that the tested isolates had good potential to colonize the rhizosphere, especially after seed inoculation. 8) According to Knief et al (2010), factors specific to the sites from which the plant species were collected, more than the plant species themselves, have a strong influence on the composition of the phyllospheric Methylobacterium community. 14) We found that PPFMs were highly abundant on perilla leaves, regardless of the geographic site from which they were collected.…”
mentioning
confidence: 99%
“…Makino) leaves (10 5{6 CFU/g of fresh leaves). Although wide distribution and isolation of PPFMs in the phyllosphere has been reported, [5][6][7][8][9][10] PPFMs of green perilla have not been reported previously. The PPFM counts of perilla were higher than those of other taxonomically closely related species such as Plectranthus, belonging to the same family Lamiaceae (Labiatae).…”
mentioning
confidence: 99%
“…Recently published data suggest that the degrees of plant-Methylobacterium association vary from very strong, as exemplified by symbioses, to semitight, as exemplified by endophytic association (7,24,41,56), to loose, as exemplified by epiphytic association on plant surfaces (6,15,40). In the case of symbiosis, the benefit for the plant is evident, in contrast to the looser forms of association between methylotrophs and plants.…”
mentioning
confidence: 99%
“…Among the methylotrophs, members of the genus Methylobacterium have been described as being ubiquitous, participating in a myriad of favorable interactions with nature (24,26,27). Furthermore, Methylobacterium spp.…”
mentioning
confidence: 99%